The Influence of Entrepreneurship Intellectual Capital in The Contribution to Economic Growth in The City of Bandung - Chairul Hakim; Titien Agustina; Arief Yanto Rukmana; Joni Hendra; Herry Ramadhani (Westscience Press, 2023)
Entrepreneurship and innovation are significant economic growth factors in cities, including Bandung, Indonesia. This study intends to investigate the impact of entrepreneurial intellectual capital on Bandung's economic growth. Using a convenience sampling technique, data were obtained from 300 Bandung entrepreneurs. Even after controlling for other characteristics such as education, age, and gender, the study discovered that entrepreneurial intellectual capital has a considerable beneficial impact on Bandung's economic growth. This research shows that officials in Bandung should prioritize fostering entrepreneurship and innovation to assist the city's economic growth.